Ductile Ni-based bulk metallic glasses at room temperature - Weiping Zeng; Yanhua Chen; Qiang Li; He Li; Baoxia Mu; Jiankang Ye; Chuntao Chang (Journal of Materials Research and Technology, 2023)
In this work, a series of new Ni76-xCoxNb4P16B4 (x = 5, 10, 15, in at.%) bulk metallic glasses (BMGs) with the maximum diameter in the range of 1.2–1.6 mm were prepared by combining fluxing and J-quenching technology. The effects of Co content on glass forming ability (GFA), thermal stability, mechanical properties, serrated-flow behaviors and corrosion performance of the present Ni-based BMGs were systematically investigated. The ranges of Tg and ΔTx are 664–668 K and 21–31 K, respectively. Uniaxial compressive tests revealed that the present Ni-based BMGs have the compressive plastic strain (εp), yield strength (δy), and fracture strength (δf) that range from 16% to 27%, 2.1–2.6 GPa, and 2.2–3.6 GPa, respectively. The unprecedented mechanical properties originate from more icosahedral-like clusters (ILCs) and crystal-like clusters (CLCs) in the present Ni-based BMGs. It is found that the serrated-flow behaviors of the present Ni-based BMGs transition self-organized critical state (SOCs) into chaotic state (Cs) as plasticity decreases. The stick-slip dynamics were used to calculate the average shear-band velocity (ASBV), which shows an increasing trend as the Co content rises from 5 at.% to 15 at.%. Electrochemical measurements in 3.5 wt.% NaCl solution showed that the Ni71Co5Nb4P16B4 BMG has a self-corrosion current density of 3.30 × 10−8 A/cm2 and significantly stronger corrosion resistance than austenite 316L and 304L stainless steel. The present Ni-based BMGs have excellent comprehensive performance, which has great potential for industrial applications.